2020
DOI: 10.1177/0193945920948469
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers of Persons with Diverse Health Conditions: Demographics and Burden of Care

Abstract: Although caregiver identity theory asserts there is no single generic caregiver identity, comparisons on demographic characteristics and burden of care have not been made among caregivers of persons with various health conditions. Using social media to access study participants, this cross-sectional study of 234 family caregivers of persons with various health conditions examined their demographic characteristics (age, gender, and race/ethnicity) and burden of care (daily care hours and caregiving years) using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Lastly, our results represent the experiences of family caregivers caring for individuals with diverse chronic and/or disabling conditions. Existing research has shown that caregiving intensity and burden depend on the health conditions of care recipients ( Zauszniewski et al, 2020 ). Future research is needed to examine whether caregiving experiences and changes to caregiving tasks are different based on care recipients’ health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, our results represent the experiences of family caregivers caring for individuals with diverse chronic and/or disabling conditions. Existing research has shown that caregiving intensity and burden depend on the health conditions of care recipients ( Zauszniewski et al, 2020 ). Future research is needed to examine whether caregiving experiences and changes to caregiving tasks are different based on care recipients’ health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the sample characteristics and measures is published elsewhere (Zauszniewski et al, 2021; Zauszniewski et al, 2021); relevant information is summarized briefly here. Data were collected using social media (i.e., Twitter and Facebook).…”
Section: Methodsmentioning
confidence: 99%
“…The study was advertised in Twitter and Facebook with the survey link. After providing online consent, caregiver participants were asked to complete demographic items, the 40 spiritual resourcefulness items and other scales used for other analyses published elsewhere (Zauszniewski et al, 2021; Zauszniewski et al, 2021). Four hundred family caregivers who met eligibility criteria enrolled as study participants.…”
Section: Methodsmentioning
confidence: 99%
“…The chance of having a low ability to complete ADL was two times higher among older adults with more than three chronic conditions ( 30 ). Conversely, aside from the number of chronic diseases, the caregiving burden may differ depending on the type of disease, diagnosis, treatment and disease progression ( 31 ). For example, previous studies have shown that of the common diseases in older people, dementia is frequently associated with a caregiving burden ( 8 , 32 ).…”
Section: Discussionmentioning
confidence: 99%